Comparative radiation performance of different feeding techniques for a microstrip patch antenna - Soh, Ping Jack; A. Rahim, Mohamad Kamal; Asrokin, A.; Abd. Aziz, Mohamad Zoinol Abidin (2005)
One of the important aspects of a microstrip patch antennas is the variety of feeding technique applicable to them. A good impedance matching condition between the line and patch without any additional matching elements depends heavily on feeding techniques used. This work is an effort to model and simulate three different types of microstrip antenna's feeding methods on a rectangular patch. Simulation is done using the circuit model derived from the transmission line model (TLM), and is compared with another simulation set of feeding methods produced using the method of moments (MoM). Both methods are simulated on Microwave Office. This design intends to focus on designing the patch and its respective feeds, simulate it using method-of-moments (MoM), and fabricate it. Radiation measurements are also presented. Designs for each feeding technique achieved the best return loss at the desired frequency range, which is 2.4 GHz. The fabricated hardware produces good return loss and comparable radiative performance with simulation using MoM.